MENINGKATKAN KETERAMPILAN BERBAHASA INGGRIS MEGGUNAKAN METODE PEMBELAJARAN TALKING STICK PADA SISWA KELAS VIII-4 SMP NEGERI 1 TIGAPANAH - RAHEL BR SITEPU (LP2MTBM MAKARIOZ, 2018)
This study aims to improve the English language skills of students of grade VIII-4 SMP Negeri 1 Tigapanah academic year 2016/2017. This study is a classroom action research with two cycles consisting of four stages: planning, action, observation and reflection. The subjects of the study were students of class VIII-4 SMP Negeri 1 Tigapanah 2016/2017 academic year as many as 33 students. The research instrument used is observation sheet of student activity and test instrument of English skill. The results showed that students' English skills increased by applying the talking stick method on formative I and formative II increased from the average value 72 to 80 and the classical completeness from 76% to 87%. So there is an increase of 11%, the data shows classical mastery in cycle II. In addition, student learning activity is also increased by applying the talking stick method shown by the percentage of active students in the first cycle of 69.7% and on the second cycle of 90.9% with an increase of 21.2%.